Pipeline integrity management and risk evaluation - Singh, Ramesh (Gulf Professional Publishing, 2017)
This book provides pipeline engineers with the tools to evaluate and inspect pipelines, safeguard the life cycle of their pipeline asset, and ensure that they are optimizing delivery and capability.